Hierarchically Structured Ni‐Enhanced Flexible Multiwall Carbon Nanotubes/Polydimethylsiloxane for a High‐Performance Pressure Sensor. Issue 23 (10th November 2021) - Bai, Yao‐Yao; Zhang, Bin; Wu, Xu‐Ping; Luo, Yan‐Wen; Bai, Zeng‐Guo; Wang, Si‐Qi; Zhang, Guang‐Ping
Abstract: Flexible pressure sensors have given rise to great research interest because of their potential applications in artificial electronic skin, wearable health‐care monitors, soft robotics, and hydrophones. However, determining how to fabricate a sensor with high sensitivity in a wide linear range by using a simple and cost‐effective manufacturing method remains a challenge. Here, a novel pressure sensor composed of a flexible substrate of multiwall carbon nanotubes (MWCNTs)/polydimethylsiloxane (PDMS) covered with a hierarchically structured Ni layer consisting of large amounts of nanoneedles and some irregular microspherical aggregates is presented. Owing to the synergistic effect of the hierarchically structured Ni layer and the special deformation behavior of the flexible MWCNTs/PDMS substrate, the as‐fabricated sensor has a high sensitivity of 10.7 kPa −1 in a wide linear range up to 15 kPa, keeping stability after 2.5 × 10 3 repeatedly compressing–releasing cycles. The sensor demonstrates sensitivity in monitoring both weak vibrations and human joint motions, which may have great potential in the field of health monitoring and electronic skin. Abstract : A novel pressure sensor composed of an electrodeposited Ni layer with tunable geometrical structures and a composite substrate of multiwall carbon nanotubes/polydimethylsiloxane (MWCNTs/PDMS) is fabricated. The performance of the sensor can be optimized by the special deformation of the MWCNTs/PDMS substrate together with a hierarchical microstructure of the Ni layer.